2003
DOI: 10.1136/vr.152.7.201
|View full text |Cite
|
Sign up to set email alerts
|

Abortion epidemic in a dairy herd associated with horizontally transmittedNeospora caninuminfection

Abstract: A dairy herd experienced an abortion epidemic during which 43 per cent of the cows at risk aborted. Neospora caninum infection was demonstrated in four of six fetuses suitable for examination and the group of at-risk cows that aborted had significantly higher N. caninum antibody concentrations than the at-risk cows that delivered a live calf at term (P<0.001). The antibody concentrations in the cow herd were significantly higher than in the youngstock (P<0.001), and the concentrations in the youngstock increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The parasite can infect a broad range of warm-blooded animals (Anderson et al 2000; Dubey, 2003; Dubey and Lindsay, 1996; Moore, 2005), but only dog (McAllister et al 1998) and coyote (Gondim et al 2004) are the definitive hosts. Cattle are the intermediate host, and N. caninum infection causes repeated abortions, stillbirths and vertical infection of calves (Anderson et al 2000; Crawshaw and Brocklehurst, 2003; Huang et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The parasite can infect a broad range of warm-blooded animals (Anderson et al 2000; Dubey, 2003; Dubey and Lindsay, 1996; Moore, 2005), but only dog (McAllister et al 1998) and coyote (Gondim et al 2004) are the definitive hosts. Cattle are the intermediate host, and N. caninum infection causes repeated abortions, stillbirths and vertical infection of calves (Anderson et al 2000; Crawshaw and Brocklehurst, 2003; Huang et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous serological survey for antibodies against N. caninum in Taiwan, we reported that 23% (3/13) of the farm dogs in Taiwan were sero-positive [17]. Thus, control of dogs in cattle farm should be considered as a measure to prevent neosporosis-associated abortion in the farm, especially preventing the dogs from eating the aborted fetus [5,7,10]. Furthermore, we also recommended that neosporosis sero-negative dairy farm should be identified and the cattle serologically tested at a regular interval to prevent suspected neosporosis-associated abortion storm.…”
mentioning
confidence: 99%